PKM Peningkatan Kompetensi Guru Melalui Pelatihan Penulisan Artikel Ilmiah Penelitian Tindakan Kelas - Sutrisno Sutrisno; Muhammad Saifuddin Zuhri (Universitas Islam Nahdlatul Ulama Jepara, 2019)
This activity aims to provide training and assistance to teachers of SMP N (State Junior High School) 1 Gubug and SMP N 2 Gubug in classroom action research as well as scientific articles. The outputs that intend to be achieved after the teachers participate in PTK training are they can compile proposals, implement PTK in the class, compile PTK reports and create scientific articles for publication. The training method is carried out by lectures and question and answer demonstrations, exercises, and practices. Training materials are presented with more practices than theories, with a ratio of 25% theory and 75% practice. The training place was held in the hall of the SMP N 1 Gubug and the SMP N 2 Gubug in Grobogan District. During the workshop, evaluation was done by post-test. The output of this service that meets the target are 80% of the teachers in both schools attended training and pass cognitive skills based on the results of post-PTK training. Meanwhile 30% of teachers in both schools were able to make proposals, and 10 of it ready to be written in scientific article to be published on journal or seminar.